Expression of carcinoma, apoptosis, and cell‐death–related genes are determinants for sensitivity of pediatric cancer cell lines to lysis by natural killer cells. Issue 10 (15th July 2019) - Ray, Anish K.; Somanchi, Srinivas S.; Dastgheyb, Neda; Aquino‐Lopez, Arianexys; Cobanoglu, Zehra E.; Geier, Brian; Lee, Dean A.
Abstract: Natural killer (NK) cells have potential utility in pediatric cancer immunotherapy for their ability to lyse diverse tumor targets, lack of dependence on mutation‐associated tumor antigens, and for their relative safety demonstrated so far in clinical trials. Here, we evaluate the cytotoxic potential of expanded NK cells against a well‐characterized panel of pediatric cancer cell lines representing Ewing sarcoma, rhabdomyosarcoma, neuroblastoma, lymphoma, leukemia, and brain tumors. We correlate their sensitivity NK cell lysis with tumor phenotypic, transcriptomic, and genetic determinants, and correlate known immunogenetic determinants with donor NK cell potency. Although ligand expression on cell lines stratified according to hematologic versus nonhematologic cancer types, the sensitivity to NK cell lysis varied widely and did not correlate with cancer type, expression of individual activating or inhibitory ligands, gene‐expression clusters of NK cell ligands, disease status (newly diagnosed or relapsed), or MYCN amplification. Rather, sensitivity to NK cell–mediated lysis was associated with a novel 96‐gene cluster of predominantly carcinoma‐, apoptosis‐, and cell death–related pathways, and with functional p53 status. NK cell potency was strongly associated with activating KIR gene content, but not with KIR/KIR‐ligand mismatch. This study suggests that adoptive immunotherapy with expanded NK cells has the potential for a wide range of pediatric cancers, identifies potential biomarkers of efficacy and response, and establishes a foundation for using this cell line panel for the preclinical evaluation of immunotherapies.